A Leagile Supply Chain Framework for Post-Disaster Relief Supplies Management in China - Zhao, Huilin (2013)
Purpose- This paper is to investigate the definition and the best practice of leagility. Meanwhile, this paper also exposes the situations of China in disaster response. The main purpose of this dissertation is to apply leagility into relief supplies distribution after earthquake.